The financial integration: An empirical analysis of Pakistan and UK - Sajid Gul; Fakhra Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
In this paper, integration of financial markets in Pakistan with those in United Kingdom, have been investigated. For this purpose we have tested the presence of co integration among Call money Rates (CMR) and t-bills rates (TBR) of Pakistan and UK. Our data consist of monthly rates of the entire domestic (Pakistan) and foreign (United Kingdom) variables. Variables selected for analysis are T-Bill Rate (TBR), Call Money Rate (CMR), Exchange Rate (Rs/) and London Inter Bank Offered Rate (LIBOR). The sample period is 1st Jan 2000, to 31st Dec 2008, which includes 96 monthly observations for each variable used. All the variables are expressed in Natural Logarithm. The sources for data collection are State Bank of Pakistan (SBP), Economic Survey of Pakistan, and IMF CD-2009. In this study we use co-integration approach to examine the integration of returns in both domestic and foreign markets. One of the pre-requisites for undertaking the cointegration framework is that the variables that are expected to have long-run relationship should have the same order of integration: For short run causality, we have estimated Vector Error Correction model. Results obtained from exchange rate are not integrating with short-term. Based on cointegration tests, the empirical results find co-integration among four variables (t-bill rate Pakistan & call money rate Pakistan, call money rate Pakistan & call money rate United Kingdom and t-bill rate Pakistan and t-bill rate United Kingdom). Vector error correction model suggested long run and short run relationship between all variables. These results thus recommend that there is a link amongst domestic and foreign market. The paper is an original work and emphasizes whether the financial liberalization undertaken in Pakistan since 2000 has created integration among domestic and foreign market. Further to analyze if there is any relation or co-movement among the rate of returns in Pakistan and UK.
Keywords: 330; T-bills rates; call money rates; financial markets; Pakistan; UK